Thin cold-mix stone mastic asphalt pavement overlay for roads and highways. (8th December 2014) - Warid, M. N. M.; Hainin, M. R.; Yaacob, H.; Aziz, M. M. A.; Idham, M. K.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper presents the latest development in the design of thin cold-mix stone mastic asphalt (SMA) pavement using modified bitumen emulsion that addresses the topmost global issues, environmental pollution and energy crisis. The hot-mix asphalt (HMA) pavement is generally known to have higher strength and is more durable compared to others, but have some disadvantages on environment, economy and safety-related issues. Cold-mix asphalt (CMA) pavements are widely used because of its simple technique and easy to construct. Currently, there are no established standards and specifications of mix design for CMA, especially for gap-graded pavement in Malaysia, and the laboratory test results are inconsistent. The use of 4·75mm nominal maximum aggregate size (NMAS) for the HMA has the highest potential for preventive and reactive maintenance of roads. Further study is needed to design and develop 4·75mm NMAS cold-mix SMA pavement in order to achieve and produce a cost-effective sustainable pavement.